Simple CTAB surfactant-assisted hierarchical lamellar MWW titanosilicate: a high-performance catalyst for selective oxidations involving bulky substrates. Issue 13 (14th June 2017) - Ji, Xinyi; Xu, Le; Du, Xin; Lu, Xinqing; Lu, Wanpeng; Sun, Junliang; Wu, Peng
Abstract : The multilamellar titanosilicate Ti-ECNU-7P and Ti-ECNU-7 with hierarchical structure were directly synthesized and proved to be more active in selective oxidations of bulky molecules. Abstract : A novel multilamellar titanosilicate composed of MWW-type nanosheets, Ti-ECNU-7P layered precursor, was directly synthesized for the first time with the assistance of boron atoms as the crystallization-supporting agent and a simple surfactant cetyltrimethylammonium bromide (CTAB) as the interlayer swelling and pillaring agent. The new Ti-ECNU-7P materials were hydrothermally synthesized readily in a wide Si/Ti molar ratio range of 10–200, when the Si/B molar ratio was 10. Ti-ECNU-7P possessed a multilamellar mesostructure, which was constructed via alternate stacking of 2.5 nm MWW zeolite nanosheets and ca. 2.4 nm CTAB molecules. This lamellar titanosilicate possessed large interlayer spacing hardly achieved by conventional hydrothermal synthesis. Subsequent acid treatment and calcination on the multilamellar precursor effectively removed the extraframework Ti species, the organic species intercalated and the majority of framework boron atoms, leading to a hierarchical titanosilicate Ti-ECNU-7 catalyst with relatively high external surface area and high concentration of Ti species on the crystal surface. The catalytic performance of hierarchical Ti-ECNU-7 nanosheets was comprehensively investigated and compared with that of typical titanosilicates in the epoxidation of various bulky alkenes with different oxidants, including aqueous H2 O2, tert -butyl hydroperoxide and cumene hydroperoxide. Owing to the hierarchical architecture and more accessible active sites on the external surface, the hierarchical Ti-ECNU-7 catalyst proved to be more active than conventional titanosilicates for selective oxidations involving either bulky substrates or oxidants. Additionally, it was robust against Ti leaching and irreversible deactivation.